Manajenem Humas Dalam Meningkatkan Citra Lembaga Pendidikan Di SMP Plus Ar Rahmat Bojonegoro - Tri Vida Kurniawati; Fathul Fauzi (At Tadbir: Islamic Education Management Journal, 2023)
This research aims to describe planning, organizing, implementing, evaluating and knowing the factors that support and inhibit public relations management in improving the image of educational institutions at SMP Plus Ar Rahmat Bojonegoro. This research uses descriptive qualitative research methods. The data collection techniques are through interview, observation and documentation techniques. The results of this research show that public relations planning for SMP Plus Ar Rahmat Bojonegoro was carried out by setting goals and creating a public relations work program. The public relations organizer of SMP Plus Ar Rahmat Bojonegoro consists of the person in charge, public relations coordinator, public relations officer, social media and communication field, and creative design field. Implementation of public relations for SMP Plus Ar Rahmat Bojonegoro by publicizing school activities. The public relations evaluation of SMP Plus Ar Rahmat Bojonegoro is held once a year and regularly weekly. The supporting factors for public relations in improving the image of educational institutions are that they are supported by good cooperation and the availability of adequate facilities and financial sources. And the inhibiting factor for public relations in improving the image of educational institutions is limited human resources